Evaluación de la amenaza por inundación del río Mocoa y río Caquetá en el sector Puerto Limón, Putumayo (Colombia) (2023)
The general objective of the study is to assess the threat of flooding in the Mocoa River and Caquetá River in the Puerto Limón sector, Putumayo (Colombia). Taking into account that the area does not have detailed information and very little information on a basic scale that allows describing the dynamics of the threat of the Mocoa River and the Caquetá River as it is a threatening factor in the sustainability of the Puerto Limón populated center.